Pathologic and genomic characteristics of myoepithelioma-like tumor of the vulvar region: three case reports - Xinyu Chen; Qingming Jiang; Jue Xiao; Mingqiong Zhang; Lili Shen (Diagnostic Pathology)
Abstract Background Myoepithelioma-like tumor of the vulvar region (MELTVR) is a rare type of soft tissue mesenchymal tumor. While MELTVR exhibits histological characteristics similar to soft tissue myoepithelial tumors, its immunohistochemical and genetic features differ significantly. To date, no comprehensive genomic analysis of this tumor has been conducted. Case presentation We present the clinicopathological features, imaging characteristics, and immunophenotypes of three patients with MELTVR, along with their genomic characterization through high-throughput sequencing. Immunohistochemical analysis revealed that these tumors were negative for SMARCB1, S-100, CD34, CD31, SMA, Desmin, and Keratin. The Ki-67 proliferation index for tumor cells ranged from 10 to 35%. Genomic analyses showed copy number deletions in the SMARCB1 gene in all three patients. The tumor mutational burden was relatively low, ranging from 1.35 to 4.33. Additionally, two tumors exhibited fusion mutations involving PPP6R3::FHDC1 and MYH9::MYH6, while no fusions involving EWSR1, NR4A3, or FUS were detected. Conclusions This study reports the first comprehensive genomic analysis of three patients with MELTVR, potentially identifying therapeutic targets for this rare tumor.